2020
DOI: 10.3390/cryst10080671
|View full text |Cite
|
Sign up to set email alerts
|

Halide Ion Embraces in Tris(2,2′-bipyridine)metal Complexes

Abstract: An analysis of the [M(bpy)3]n+ (bpy = 2,2′-bipyridine) complexes with halide counterions in the Cambridge Structural Database reveals a common structural motif in two thirds of the compounds. This interaction involves the formation of 12 short C–H…X contacts between halide ions lying within sheets of the cations and H-3 and H-3′ of six [M(bpy)3]n+ complex cations. A second motif, also involving 12 short contacts, but with H-6 and H-5, is identified between halide ions lying between sheets of the [M(bpy)3]n+ ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…The remaining 44 solid-state structures fell into categories of mononuclear (33) and dinuclear (11) species, including several redeterminations at either the same or different temperatures. We consider these groups of structures separately in the following discussion.…”
Section: Defining the Sets Of Structures For Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining 44 solid-state structures fell into categories of mononuclear (33) and dinuclear (11) species, including several redeterminations at either the same or different temperatures. We consider these groups of structures separately in the following discussion.…”
Section: Defining the Sets Of Structures For Analysismentioning
confidence: 99%
“…More recently, using data from the Cambridge Structural Database (CSD) [10], we demonstrated the significance of short contacts between atoms H3 and H3 of the bpy ligands in [M(bpy) 3 ] q+ and the counterion (see Scheme 3 for atom numbering) which may be augmented by interactions of the anion with bpy atoms H4 and H5. This combination of CH...X contacts results in anions residing either in the center or lying above and/or below the centroid of the hexagonal {M(bpy) 3 } 6 motif [11,12]. We extended these investigations to octahedral cis-[M(bpy) 2 X 2 ] coordination compounds and showed that a recurrent packing motif is a dimeric unit containing CH bpy ...X contacts and intermolecular face-to-face π-stacking of bpy ligands; in some cases, CH bpy ...X contacts are the dominant features of the crystal-packing [13].…”
Section: Introductionmentioning
confidence: 99%
“…2,2′-Bipyridine (bipy) has become one of the most recognizable and commonly used bidentate N,N-chelating ligands in coordination chemistry since its discovery by Fritz Blau in 1888. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Pioneering works on coordination compounds with bipy provided chemists with first insights into the thermodynamics and kinetics of metal ion complexation, metal-ligand bonding properties, and photo-, magneto-, and electrochemistry of metal complexes. Over two centuries, all these studies have played a pivotal role in the development of our modern understanding of the fundamental aspects of coordination chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…2,2'-Bipyridines are the commonly used ligands for different metal cations [1,2]. In case of the presence of polyaminocarboxylic acid (DTTA, DO3A etc.)…”
Section: Introductionmentioning
confidence: 99%